2021
DOI: 10.3389/fgene.2021.679363
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-6 Signaling and C-Reactive Protein With Intracranial Aneurysm: A Mendelian Randomization and Genetic Correlation Study

Abstract: Background and objectiveEvidence suggests that interleukin-6 (IL6) signaling is causally associated with aortic aneurysm independently of the effect of C-reactive protein (CRP). We aimed to explore the genetic overlap and associations between inflammation (IL6 signaling and CRP) and intracranial aneurysm (IA) risk.MethodsTwo-sample Mendelian randomization (MR) methods were used to assess the causal effects of soluble IL6 receptor (sIL6R) (n = 21,758) and CRP (n = 204,402) levels on IA (7,495 cases and 71,934 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Result of the present study was consistent with previous research which observed significantly higher cerebrospinal fluid level of GRO-alpha in uIA patients [ 50 ]. Our result was supported by a previous MR study which showed sIL6R and CRP levels were not associated with IA [ 8 ]. Our finding was partially contradictory to a meta-analysis, which found no evidence of IL-1α, IL-1β, IL-6, and IL-12β against IA, but identified significant association of TNF-α polymorphism with IA [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Result of the present study was consistent with previous research which observed significantly higher cerebrospinal fluid level of GRO-alpha in uIA patients [ 50 ]. Our result was supported by a previous MR study which showed sIL6R and CRP levels were not associated with IA [ 8 ]. Our finding was partially contradictory to a meta-analysis, which found no evidence of IL-1α, IL-1β, IL-6, and IL-12β against IA, but identified significant association of TNF-α polymorphism with IA [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have utilized MR to explore the casual relationship between IA and various risk factors, with only one study examining potential inflammatory mechanism. With a hypothesis-driven design, previous MR study have revealed sIL6R and C-reactive protein (CRP) levels were not associated with IA risk [ 8 ]. Given these uncertainties, we designed this MR study to further assesses whether causality exists between inflammatory biomarkers and IA.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we preliminarily assessed the genetic overlap between EoE and IBD (data from the ieu-a-31 GWAS dataset) via the linkage disequilibrium score regression ( 38 ), and the result showed no evidence of a genetic correlation between the two diseases (genetic correlation = −0.325, p = 0.393). Generally, a consistency between results of linkage disequilibrium score regression and MR could make the MR estimates more convincing ( 39 ). Therefore, results generated by this study should still be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies demonstrating such associations. A study examining soluble IL-6 receptor and CRP levels to intracranial aneurysm risk showed no association despite other studies showing high CRP levels related to fusiform intracranial aneurysm presence and IL-6 polymorphisms related to intracranial aneurysm presence [16][17][18]. Additional cytokines have been examined in healthy patients with intracranial aneurysms, noting elevated levels of IL-1B, TNF-alpha, and MCP-1 in those with aneurysms [19].…”
Section: Discussionmentioning
confidence: 99%